2015
DOI: 10.1007/s13157-015-0665-z
|View full text |Cite
|
Sign up to set email alerts
|

Changing Water Quality in the Middle Mahakam Lakes: Water Quality Trends in a Context of Rapid Deforestation, Mining and Palm Oil Plantation Development in Indonesia’s Middle Mahakam Wetlands

Abstract: The degradation of Indonesia's wetlands is continuing at a rapid pace. People living in the Middle Mahakam Lakes (MML) region, part of a major wetland area in Indonesia, have observed various negative changes in their local environment, especially with regard to water quality. We verify these local perceptions with the support of water quality measurements (physical and chemical) taken in 1992-93, 1995, 1998 and 2006. We also aim to present data that can be used to determine future trends. We evaluated the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…First, the lake water near both villages seemed to be particularly affected. The lake water around Ohong showed extremely low values of dissolved oxygen, which could prove lethal for fish, while we found low alkalinity levels in Enggelam, triggered by an increased acidic input, possibly as a consequence of deforestation, mining activities, or the drainage of peatlands [5]. Second, there were notable differences in people's perspectives on the changes in the environment.…”
Section: Methods and Analysismentioning
confidence: 65%
See 3 more Smart Citations
“…First, the lake water near both villages seemed to be particularly affected. The lake water around Ohong showed extremely low values of dissolved oxygen, which could prove lethal for fish, while we found low alkalinity levels in Enggelam, triggered by an increased acidic input, possibly as a consequence of deforestation, mining activities, or the drainage of peatlands [5]. Second, there were notable differences in people's perspectives on the changes in the environment.…”
Section: Methods and Analysismentioning
confidence: 65%
“…In Enggelam, the picture was far more varied: while about half of the population thought that the quality of the water had deteriorated, 38% had not noticed any change and a little over 10% even perceived positive changes in the water quality. Our earlier measurements had found that the lake water at both locations was very acidic, akin to swamp conditions, with very low oxygen levels; see [5]. When asked about the reasons for the changes, many villagers blamed the mining companies and plantation enterprises, although over one-third did not know why these changes had occurred or would refer to Allah as the source and cause of climatic changes.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The palm oil industry is a major water polluter in Southeast Asia because uses large amounts of fertilizers (Muyibi et al, 2008), and discharge POME (Wu et al, 2010) to aquatic ecosystems; a challenge for Indonesian (de Jong et al, 2015;Comte et al, 2015). According to Saswattecha et al (2015) five most activities in palm oil field that contribute negative impact onto environmental are: burning fibers in boilers, use of fertilizers, wastewater treatment and empty-fruit-bunch disposal, gasoline in weed cutters and glyphosate for control of weed.…”
Section: Component Of Water Usagedmentioning
confidence: 99%